The in vitro stimulatory activity of CwlM∼P on mycobacterial MurA depends on a charged predicted interface that is distal from the CwlM phosphorylation site - Hunt-Serracin, Augusto Cesar; Tembiwa, Karen E.; Awagu, Arinze; Ghaffari, Soroush; Kang, Katie N.; Boutte, Cara C. (Frontiers in Microbiology, 2025)
Mycobacterium tuberculosis and other mycobacteria have a thick cell wall that is tightly regulated - ensuring cell integrity and promoting antibiotic tolerance. The peptidoglycan layer of the cell wall is controlled at multiple points along the synthesis pathway. Here we focus on the stimulation of the peptidoglycan precursor enzyme MurA by its regulator CwlM. Using AlphaFold2 Multimer predictions we predicted a charged regulatory interface between CwlM and MurA that is separate from the phosphorylation site on CwlM that was previously shown to be required for activation. Using mutants of CwlM, we found that all of CwlM∼P’s stimulation of MurA activity is dependent on this charged interface in vitro. However, our in vitro results here and previously suggest that MurA may require activators besides CwlM∼P to be fully active. Our in vivo studies of the CwlM charged interface mutants corroborate this: we observed no defects in growth and only mild defects in peptidoglycan metabolism. Our findings suggest that MurA regulation by CwlM involves at least two sites on the CwlM protein, and that regulation of MurA in vivo is only modestly affected by CwlM, and likely involves other, unknown regulatory factors.